HUBUNGAN KOMPENSASI FINANSIAL DAN STRES KERJA DENGAN KINERJA KARYAWAN PT. DOK DAN PERKAPALAN SURABAYA (PERSERO) - Mita Desy Yani; Endang Dwiyanti (Universitas Airlangga, 2016)
The worker performance must be considered by company due to worker who have good performance can help the company to achieve its goal. Company should give responsibilities according to workers’s ability and expertise for making good performance. The ups and down of worker performance happened because of the tough workload, uncomfortable work environment, and unfilled employee demands. This research analyzed the correlation between financial compensation and work stress on worker performance in PT. Dok and Perkapalan Surabaya (Persero). This research was descriptive which collected observationally with cross-sectional design. The population of study was construction worker in PT. Dok dan Perkapalan Surabaya (Persero), the sample was taken by total population which is consist of 40 workers. Independent variables were financial compensation and work stress. Dependent variable was worker performance. The primary data using questionnaires, observation, and interview while secondary data was profile company. The result from questionnaires were calculated using Spearman correlation. It showed that correlation level between financial compensation and worker performance was moderate with 0.332 correlation coefficient value. The level of correlation between work stress toward worker performance is moderate with 0.445 correlation coefficient value. It suggested to industry to improve the concern toward worker by creating safe and comfortable work environment. Giving reward to worker who has good achievement or who can create something useful for company.Keywords: compensation financial, work stress, worker performance